Hydrologic balance in an intact temperate forest ecosystem under ambient and elevated atmospheric CO 2 concentration - Karina V. R. Schäfer; Ram Oren; Chun‐Ta Lai; Gabriel G. Katul (Global Change Biology, 2002)
Increasing atmospheric CO 2 concentration decreases stomatal conductance in many species, but the savings of water from reduced transpiration may permit the forest to retain greater leaf area index ( L ). Therefore, the net effect on water use in forest ecosystems under a higher CO 2 atmosphere is difficult to predict. The free air CO 2 enrichment (FACE) facility ( n = 3) in a 14‐m tall (in 1996) Pinus taeda L. stand was designed to reduce uncertainties in predicting such responses. Continuous measurements of precipitation, throughfall precipitation, sap flux, and soil moisture were made over 3.5 years under ambient (CO 2 a ) and elevated (CO 2 e ) ambient + 200 µmol mol −1 ). Annual stand transpiration under ambient CO 2 conditions accounted for 84–96% of latent heat flux measured with the eddy‐covariance technique above the canopy. Under CO 2 e , P. taeda transpired less per unit of leaf area only when soil drought was severe. Liquidambar styraciflua , the other major species in the forest, used progressively less water, settling at 25% reduction in sap flux density after 3.5 years under CO 2 e . Because P. taeda dominated the stand, and severe drought periods were of relatively short duration, the direct impact of CO 2 e on water savings in the stand was undetectable. Moreover, the forest used progressively more water under CO 2 e , probably because soil moisture availability progressively increased, probably owing to a reduction in soil evaporation caused by more litter buildup in the CO 2 e plots. The results suggest that, in this forest, the effect of CO 2 e on transpiration was greater indirectly through enhanced litter production than directly through reduced stomatal conductance. In forests composed of species more similar to L. styraciflua , water savings from stomatal closure may dominate the response to CO 2 e .

Modelling night‐time ecosystem respiration by a constrained source optimization method - Chun‐Ta Lai; Gabriel Katul; John Butnor; David Ellsworth; Ram Oren (Global Change Biology, 2002)
One of the main challenges to quantifying ecosystem carbon budgets is properly quantifying the magnitude of night‐time ecosystem respiration. Inverse Lagrangian dispersion analysis provides a promising approach to addressing such a problem when measured mean CO 2 concentration profiles and nocturnal velocity statistics are available. An inverse method, termed ‘Constrained Source Optimization’ or CSO, which couples a localized near‐field theory (LNF) of turbulent dispersion to respiratory sources, is developed to estimate seasonal and annual components of ecosystem respiration. A key advantage to the proposed method is that the effects of variable leaf area density on flow statistics are explicitly resolved via higher‐order closure principles. In CSO, the source distribution was computed after optimizing key physiological parameters to recover the measured mean concentration profile in a least‐square fashion. The proposed method was field‐tested using 1 year of 30‐min mean CO 2 concentration and CO 2 flux measurements collected within a 17‐year‐old (in 1999) even‐aged loblolly pine ( Pinus taeda L.) stand in central North Carolina. Eddy‐covariance flux measurements conditioned on large friction velocity, leaf‐level porometry and forest‐floor respiration chamber measurements were used to assess the performance of the CSO model. The CSO approach produced reasonable estimates of ecosystem respiration, which permits estimation of ecosystem gross primary production when combined with daytime net ecosystem exchange (NEE) measurements. We employed the CSO approach in modelling annual respiration of above‐ground plant components ( c. 214 g C m −2 year −1 ) and forest floor ( c. 989 g C m −2 year −1 ) for estimating gross primary production ( c. 1800 g C m −2 year −1 ) with a NEE of c. 605 g C m −2 year −1 for this pine forest ecosystem. We conclude that the CSO approach can utilise routine CO 2 concentration profile measurements to corroborate forest carbon balance estimates from eddy‐covariance NEE and chamber‐based component flux measurements.